2021
DOI: 10.3390/su13084420
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Use of Serious Games for Enhancing Community Resilience to Climate Risks in Thailand

Abstract: This paper presents the ‘Kin Dee You Dee’ (Thai for ‘Eat well, live well’) toolkit, which comprises three sets of serious games aimed at facilitating discussions and transformative learning on resilience to urban low-income communities. The first stage of the toolkit creates awareness of key concepts related to resilience, the second stage allows participants to map individual and community assets and identify risks associated with them, and the final stage encourages participants to reflect upon potential thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…While indicating that the use of games gave them more space to co-design collective solutions, the residents also expressed that this method offered opportunities to connect adaptation strategies to their values and immediate needs. This example demonstrates that the implementation of informal settlement upgrading projects requires the creation of "safe space" that can offer visibility to underrepresented livelihoods (Marome et al, 2021).…”
Section: From Informative To Consultative Approachesmentioning
confidence: 98%
See 2 more Smart Citations
“…While indicating that the use of games gave them more space to co-design collective solutions, the residents also expressed that this method offered opportunities to connect adaptation strategies to their values and immediate needs. This example demonstrates that the implementation of informal settlement upgrading projects requires the creation of "safe space" that can offer visibility to underrepresented livelihoods (Marome et al, 2021).…”
Section: From Informative To Consultative Approachesmentioning
confidence: 98%
“…Serious games are defined as games to engage communities to deliver specific objectives (e.g., pedagogical, or problemsolving purposes) and operating beyond the realm of entertainment (Abt, 1970). In the case study of Kin Dee You Dee ('Eat well, live well') in Thailand, serious games have have been used to engage local communities in the discussion of climate change adaptation strategies (Marome et al, 2021). The experience revealed that serious games can serve as a method to sensibly consider local needs in the context of informal settlement upgrading projects.…”
Section: From Informative To Consultative Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…By making a balance between learning and fun, serious games for learning are recognized as a powerful and persuasive tool, encouraging participation, ideation, and discussions among stakeholders. Covering a wide range of forms and mediums, serious games can play a significant role in community building and engagement [6], in the promotion of participatory design [7], in raising risk awareness, and in stimulating decision making and behavior change [8]. Games also can build capability and capacity to train in safe innovation spaces and interactively engage with alternate climate futures [6].…”
Section: Introductionmentioning
confidence: 99%
“…Covering a wide range of forms and mediums, serious games can play a significant role in community building and engagement [6], in the promotion of participatory design [7], in raising risk awareness, and in stimulating decision making and behavior change [8]. Games also can build capability and capacity to train in safe innovation spaces and interactively engage with alternate climate futures [6].…”
Section: Introductionmentioning
confidence: 99%